Enhancing women's engagement in entrepreneurial business activities - Natasha Ristovska; Daliborka Blazheska (UTMS Journal of Economics, 2020)
Women have a great influence in all spheres of the society that is continuously growing nowadays, with their significant professional achievements even in certain sectors that were reserved for men. The development of women entrepreneurship varies in different parts of the world depending on the economic development of the region. However, the engagement of women in entrepreneurial activities strengthens their economic power. The purpose of this paper is to elaborate the motivation for women to start their own businesses, focusing on specific problems and challenges they need to face and overcome, as well as to analyse the development of women position in business and society. The importance of entrepreneurial education, changing stereotips for women and support from successful women by sharing their story and experience, is also highlighted. A situation analysis based on comparaison of women holding leading managerial positions and their business involvement in different countries is provided. The reserach is supported by survey conducted in North Macedonia on representative number of 50 women entrepreneurs in order to identify the most important factors for ehancing the development of women entrepreneurship.
Keywords: M13; L26; 330; entrepreneurship; business development; woman; empowerment